Initial reconnaissance for a South Georgia ice core - Mayewski, Paul A.; Kuli, A.; Casassa, G.; Arévalo, M.; Dixon, D. A.; Grigholm, B.; Handley, M. J.; Hoffmann, Helene; Introne, D. S.; Kuli, A. G.; Potocki, M.; Sneed, S. B. (Journal of glaciology, 2016)
We present the first snow/ice chemistry and ice radar results ever collected from South Georgia as part of an initial reconnaissance with the ultimate goal of assessing the feasibility of a South Georgia ice core to reconstruct past climate in the South Atlantic. South Georgia is well situated to capture a record of past atmospheric chemical composition over the South Atlantic and of past variability in the position and intensity of the austral westerlies. The question is how well preserved an ice core record can be recovered from a region experiencing accelerated melting? The results presented in this paper offer only a preliminary step in determining the feasibility of future deep ice coring on South Georgia. However, this initial reconnaissance does provide some basic information including: the chemistry of the atmosphere over South Georgia relative to other Southern Hemisphere ice coring sites; the potential for preservation of ‘annual layers’ in old ice on the island; a possible age for deep ice in the region; and an estimate of glacier health in the lower elevation regions of the island.